Band Structure Engineering of Black Phosphorus/Graphene/MoS2 van der Waals Heterojunctions for Photovoltaic and Optoelectronic Device Application. Issue 2 (April 2021) - Zhu, Wenhuan; Kong, Lingwei; Long, Wei; Shi, Xianglei; Zhou, Dayong; Sun, Lijie; Zhou, Lihua; Yang, Guiting; Liu, Xiaodong; Liu, Hai; Bo, Maolin; Hou, Xiaoqiang
Abstract: In this paper, we study the band structure engineering of black phosphorus/graphene/MoS2 (BP/graphene/MoS2 ) van der Waals heterojunctions based on ab initio simulations. The density of state and charge density of BP/MoS2, bilayer-BP/MoS2, bilayer-BP/graphene/MoS2 and graphene/bilayer-BP/MoS2 heterojunctions are also investigated. It is found that the bandgaps of these four heterojunctions are smaller than the case of single layer BP or MoS2 . When graphene is inserted into or stacked upon BP and MoS2 layers, the heterojunction can obtain a minimum bandgap and a higher density of state distribution. In the differential charge density diagram, electrons over the carbon, sulfur and phosphorus atoms are lost from those corresponding parts. These investigations based on the band structure engineering of 2D van der Waals heterojunctions can provide an effective guidance to manufacture the future nanoscale high performance photovoltaic and optoelectronic devices.